ChemInform Abstract: A Catalyst‐Free C—H Hydroarylation of Coumarin‐Derived ortho‐Quinone Methide (o‐QM) with Electron‐Rich Arenes in Glycerol. Issue 11 (8th March 2013) - Kumar, Atul; Kumar, Mukesh; Gupta, Maneesh Kumar; Gupta, Lalit Prakash
Abstract The methide obtained from the carbonyl‐containing substrates with aromatic or aliphatic aldehydes is further treated with tertiary aromatic amines to produce the different types of products shown.